CBMT-34. MODULATING DIETARY TRYPTOPHAN OR GUT MICROBIOTA LEVELS DOES NOT IMPROVE THE EFFICACY OF COMBINED TREATMENT WITH RADIATION, ANTI-PD-1 mAb, AND AN IDO1 ENZYME INHIBITOR IN A MODEL OF GLIOBLASTOMA. (11th November 2019) - Ladomersky, Erik; Zhai, Lijie; Lauing, Kristen; Qian, Jun; Bell, April; Otto-Meyer, Sebastian; Savoor, Rohan; Wainwright, Derek
Abstract: INTRODUCTION: Immunotherapy has failed to improve glioblastoma (GBM) patient survival in all phase III clinical trials to-date. We recently discovered that a combination immunotherapeutic approach that simultaneously administers radiation (RT), anti-PD-1 mAb, and an IDO1 enzyme inhibitor resulted in long-term survival of 40% of mice intracranially-engrafted (i.c.) with syngeneic GBM (Ladomersky et al ., 2018; CCR). In the same study we discovered that the survival benefit depended on the inhibitor of IDO1 in non-GBM cells. Our current study further interrogates the role of non-GBM cell IDO1 and its role in the brain tumor microenvironment. METHODS: Mice were engrafted with 2×10 5 GL261 cells and treated at 14 days post-intracranial injection (i.c.) with RT and/or anti-PD-1 mAb, followed by sampling tissue at 1- and 7-days post treatment. Questioning whether dietary supplementation of Trp would overcome the immunosuppressive activity of the Trp metabolic enzyme, IDO1, mice were placed on ad libitum dietary formulations containing 0–500% normal daily intake. Since Trp is only taken in through the diet, and since bacteria also metabolize Trp, we questioned the role of the gut microbiome on immunotherapy of GBM by injecting mice with an antibiotic cocktail beginning 4 weeks prior to i.c.-injection. RESULTS: Both RT and anti-PD-1 treatment increase IDO1 expression in the GBM-draining cervical lymph nodes at day 1 post-ic. ( P < 0.001). Mice receiving normal (100%) dietary Trp, but no other supplementation levels, achieve a long-term survival benefit ( P < 0.001). Unexpectedly, the depletion of gut microbiota has no effect on therapeutic efficacy ( P =0.4808). CONCLUSION: These data suggest that although both systemic and tissue-selective alterations in Trp metabolism occur after RT and anti-PD-1 therapy, modulating dietary Trp levels or gut microbiota composition does not alter treatment efficacy against GBM.